PENGEMBANGAN BUKU PANDUAN PRAKTIKUM BERBASIS INKUIRI TERBIMBING UNTUK GURU PADA PEMBELAJARAN BIOLOGI KELAS XII SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to develop a guided inquiry-based practicum guidebook for teachers in teaching biology at the first year of senior high school students. It was conducted in october 2020 to december 2021. The model used in this research is a ADDIE model. Model consists of 5 (five) stages, namely analysis, design, development, implementation and evaluation. This research was carried out until stage 3 (three), namely the development stage. The stage of analyze, design, development, internal validation and limited trial phase I was carried out in the Biology Education Laboratory FKIP University of Riau. External validation was carried out in SMA Negeri 1 Bintan Timur and SMA Negeri 1 Teluk Sebong. The book is validated based on five indicators, namely: book format, graphics, illustrations and pictures, language, and content eligibility. The overall results of the validation obtained an average of 3,46 with very valid categories. The results of the limited trial phase I have an average of 3,60 with very good categories and the results of the limited trial phase II have an average of 3,60 with very good categories. The book produced in this study has a very valid and very good categories so that the practicum guidebook is broad to hold the teacher’s grip in proper and can be implementation of practical activities. Key Words: Practical Guidebook, Guided Inquiry, Biology Learning